Board independence and corporate social responsibility disclosure: The mediating role of the presence of family ownership - Shashank Bansal; Maria Victoria Lopez-Perez; Lazaro Rodriguez-Ariza (Administrative Sciences, 2018)
This paper examines the impact of board independence on corporate social responsibility (CSR) disclosure and analyses the moderating effect of the presence of family ownership. Using an international sample from 29 countries from 2006 to 2014, our panel Tobit estimation shows that board independence is negatively associated with CSR disclosure practices and they present opposition to CSR disclosure practices. However, family ownership moderates the relationship and enforces the positive orientation of independent directors towards CSR disclosure. This shows that the presence of family ownership reduces independent director concern of reputation risks associated with receiving misleading information and family firms decrease the asymmetries of information between the independent director and management. The study also finds that independent directors encourage CSR disclosure in family firms more in civil law countries where investor protection is low compared to common law countries where investor protection is high.
Keywords: 350; family business; independent directors; corporate social responsibility; voluntary disclosure